Teaching research group leaders’ perceptions of their engagement in curriculum leadership - Shan, Yiming; Chen, Junjun (Frontiers in Psychology, 2022)
Understanding how teacher leaders are engaged in curriculum affairs is critical with the implementation of instructional decentralization. The current study adopts a qualitative approach to investigate Teaching Research Group (TRG) leaders’ involvement in curriculum leadership (CL) in the Chinese context. It explores the conceptions of TRG leaders by interviewing 20 of them, observing four meetings held by TRG leaders, and collecting 10 extracts from appraisal summaries of TRG leaders in secondary schools in China. Drawing on the findings, this paper examines the characteristics of TRG leader’s engagement in CL. More importantly, data highlighted significant problems the participants perceived and faced in their work as TRG leaders, which consisted of amplifying the necessity for empowering TRG leaders and identifying the phenomenon that said leaders are less empowered and less motivated to undertake the CL role. The results add to the international body of knowledge on the teachers’ engagement in CL.